Pelaksanaan Metode Talaqqi dalam Program Tahfidz Al-Qur'an bagi Peserta Didik di SMA Pembangunan Laboratorium UNP - Anggun Mursyida; Rini Rahman (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The Talaqqi method is a method of memorizing the Qur'an which is done by listening to the verses of the Qur'an read directly by a teacher who memorizes the Qur'an. Talaqqi is a way to learn to memorize the Koran directly to people who are proficient at reading the Qur'an. This study aims to determine the implementation of the Talaqqi method in the Tahfidz Qur'an program for students at UNP Laboratory Development High School. This study uses a qualitative method with a case study approach, data sources were taken from ten informants (the principal, two tahfidz teachers, and seven students) through direct interviews, observation, and documentation. Then the data were analyzed using the Miles and Hubermen model analysis techniques. The results showed that the implementation of the Talaqqi method in the Tahfidz Qur'an program for students at the UNP Laboratory Development High School included (1) Determining the schedule for the tahfidz program once a week with 2 hours of learning, (2) Preparing a work program. (3) Implementing the Talaqqi method (4) Evaluation of the Talaqqi method includes: First, in teacher assessment it focuses on makhrojul letters, tajwid reading, and makhom. Second, the teacher replaces the steps of the Talaqqi method. Third, the teacher combines the Talaqqi method with other tahfidz methods.